2015
DOI: 10.3389/fneur.2015.00111
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles: What is the Role in Multiple Sclerosis?

Abstract: Microvesicles are a recently described way of cell communication that has been implicated in a number of biological processes, including neuroinflammation. Widely investigated as biomarkers in oncology and neurological disorders, little is known of the role of microvesicles in the pathogenesis of diseases such as multiple sclerosis (MS). Several evidences suggest that pro-inflammatory microglia and infiltrating macrophages release microvesicles that spread inflammatory signals and alter neuronal functions. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…EVs derived from both microglia and astrocytes have an active role in neuroinflammation, in part by spreading proinflammatory signals; for example, during multiple sclerosis (MS), a demyelinating disease 84,85 . Such microvesicles contain pro-inflammatory cytokine IL-1β, interferon-γ, tumour necrosis factor (TNF), caspase 1 and the P 2 X 7 receptor, among others.…”
Section: Evs In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…EVs derived from both microglia and astrocytes have an active role in neuroinflammation, in part by spreading proinflammatory signals; for example, during multiple sclerosis (MS), a demyelinating disease 84,85 . Such microvesicles contain pro-inflammatory cytokine IL-1β, interferon-γ, tumour necrosis factor (TNF), caspase 1 and the P 2 X 7 receptor, among others.…”
Section: Evs In Diseasementioning
confidence: 99%
“…Deciphering the mechanisms that trigger EV release, promote EV uptake, provide cell target specificity and determine cargo selectivity is critical to the development of EVs as therapeutic agents in a clinical setting. Second, given that evidence suggests that exosomes also have the potential to spread nefarious factors, such as prion-like proteins 110 and pathological inflammation 84,85 , as discussed above, as well as viruses 111 , many safety concerns for their use in the clinic remain. Although the idea of generating artificial EVs is attractive, a more thorough understanding of EV biology will be paramount to their construction and use as a Trojan horse to combat disease.…”
Section: Evs In Diseasementioning
confidence: 99%
“…In addition, other studies reported that mast cell-derived exosomes containing MHC class II molecules could also stimulate T-cells (Vincent-Schneider et al 2002). Interestingly, a recent study has reported that exosomes derived from microglia/macrophages resident in the CNS are involved in spreading pro-inflammatory signals, altering neuronal function and therefore contributing to pathogenesis of multiple sclerosis (MS) (Carandini et al 2015). Pathogen-infected cells can also secrete exosomes that carry antigens from pathogens and stimulate specific CD4+ and CD8+ T-cell responses (Bhatnagar & Schorey 2007, Walker et al 2009).…”
Section: Exosomesmentioning
confidence: 99%
“…Several proteins, nucleic acids, and (glyco)‐lipids have been proposed as candidate biomarkers for MS, but none of them are routinely applied in clinical practice. These molecules could circulate freely in body fluids, associated with carrier proteins, lipoproteins, or EVs of different sizes and composition (Carandini et al, ). Relevant aspects of EVs have been described in MS and other neurological diseases, and although many features of their biological function need further investigation, these vesicles represent attractive targets to be used for diagnostic and/or therapeutic purposes (Candelario and Steindler, ; Harris and Sadiq, ; Westphal and Lamszus, ).…”
Section: Introductionmentioning
confidence: 99%